Tuberculose na população privada de liberdade : características clínicas e epidemiológicas relacionadas à doença - Macêdo, Laylla Ribeiro (2014)
Introduction: There are about two decades, tuberculosis (TB) was considered by the World Health Organization (WHO) as a disease in a state of emergency throughout the world. Currently, despite all efforts to control the disease, yet it is an important public health problem, showing strong relationship with socioeconomic issues, which entail greater illness in specific groups, such as prisoners. Data for TB in vulnerable populations can achieve even higher levels and therefore worrying. Objectives: To analyze the clinical and epidemiological characteristics associated with the outcomes of tuberculosis treatment in the prison population of Brazil, registered in the Information System for Notifiable Diseases (SINAN), 2007-2011; understand the incidence and mortality TB in prisoners of the state of Espírito Santo from July 2009 to July 2010 , and to identify the clinical and epidemiological characteristics of all diagnosed cases of tuberculosis in prisoners of the Holy Spirit , from July 2009 to July 2010. Methods: The study population consisted of diagnosed inmates with identified tuberculosis through SINAN, between January 2007 and December 2011 and diagnoses cases of tuberculosis among inmates of the Espírito Santo in the period from 1st July 2009 to 30 June 2010. The chi - square test and polynomial regression model were used to analyze, in addition to descriptive statistics, through tables and graphs. Results: Compared with patients in TB prisoners in Brazil, it is noted that prisoners who abandoned treatment were younger (P < 0.001), less educated (P < 0.001) and greater likelihood of alcoholism (P < 0.001), were more likely to have recurrent TB or recurrence (P < 0.001) and they were not under directly observed treatment (P < 0.001) compared with those who completed the treatment of tuberculosis. Those who died of tuberculosis tend to be older (P < 0.001) and alcoholics (P < 0.001) were also more likely to unknown type of treatment (P < 0.001) and presenting pulmonary TB and extrapulmonary TB (EPTB). Prisoners who developed MDR TB were more likely to experience recurrence of TB, return after default and transfer of the treatment site. Furthermore, we observed 167 cases of tuberculosis (incidence rate of 1962.6 per 100,000 inmates) in Espírito Santo. Males showed a higher number of patients, as well as the age group of 25-36 years and the pulmonary form. It is noteworthy that 109 (65.3 %) patients were discharged as cured, two patients died during the period, with the rate of tuberculosis mortality of 11 11.7 per 100,000 inmates. The highest incidence of tuberculosis in patients was located in the prisons of the metropolitan area and a small number of cases occurred in other sites out of prisons. Conclusion: Our results highlight the need to improve policies for TB control in prisons, as well as the outcomes of the treatment of prisoners in order to prevent transmission to other inmates, their families and health professionals.